COMPARISON OF THE INCIDENCE OF HYPOCALCEMIA IN THYROIDECTOMY DUE TO MULTI-NODULAR GOITER AND THYROID CANCER - Mansourian, A.; Paymard, A.; Khastavaneh, M.; Parvizian, R.; Jahantab, M. (University of Eloued جامعة الوادي, 2018)
Introduction: Thyroid disease, especially nodular lesions, is one of the most common diseases in recent years. Non-toxic nodular goiter multinodular is a common thyroid problem, which increases with increasing age. Multi-nodular malformation can cause Excessive glandular enlargement and more than any other thyroid disease with glandular neoplastic involvement. In fact, multi-nodular goiter is benign, but there are some focal regions of malignant changes that cannot be detected by physical examination, ultrasonography, or radioisotope scanning, and only after extraction of the tuber by surgery and its pathological examination. Method: This descriptive-analytic study was a retrospective study in which 180 patients underwent total thyroidectomy, which was the cause of this multi-nodular goiter or thyroid cancer. This study was conducted to investigate the patients referred to Shahid Beheshti Hospital in 2016 and 2017. Meanwhile, 86% of the patients were female with thyroidectomy. The cause of thyroidectomy was multiple nodular goiter and thyroid cancer. The cause of the action was based on the case, the description of the practice and the doctor's opinion, as well as the answer to the pathology sample. In order to select the sample, all files of patients under complete thyroidectomy were selected and counted. Discuss: The aim of this study was to compare the incidence of hypocalcaemia in thyroidectomy with the cause of multiple nodular goiter and thyroid cancer. The first finding from the present study was that there was no significant difference in incidence of hypocalcemia in thyroidectomy due to MNG and thyroid carcinoma. Since surgery has been performed in a university hospital with a large number of patients and has been carried out by surgeons with sufficient surgical experience and skill, there is no significant difference in the incidence of hypocalcemia in thyroidectomy due to the multi-nodular goiter and thyroid cancer, as a result of this issue. Conclusion: The results of this study showed that there is no difference between the incidence of hypocalcemia in thyroidectomy and the cause of multinodulargoiter and thyroid cancer.
Article in Journal of Fundamental and sciences. university of el oued
Keywords: hypocalcemia, thyroidectomy, multi-nodular goiter